ANALYSIS OF THE EFFECT OF PROMOTION THROUGHT SOCIAL NETWORKS ON SALES AT KLINIK SELERA IN BANGKINANG CITY - Yola Alwitri; Librina Tria Putri; Litra Diantara (STIE Bangkinang Publishing, 2020)
This research aims to determine the effect of promotion throught social networks on sales at Klinik Selera in Bangkinang City. This research was conducted at the Klinik Selera in Bangkinang City which is located on Profesor M. Yamin Bangkinang Sub-District, Kampar Regency, with a research time of two months, namely in May and July 2020. While types and sources of data used in this study are primary data and secondary data, while data collection techniques used in this study were questionnaires, file research, observation and interviews. Sampling was done bg accidental sampling method which is a sampling technique based on coincidence so that number of samples in this research were 100 consumers. Data analysis carried out by simple linear regression model and hypothesis testing carried out by the t test at the rate of 5%. Based on the result of the research it can be concluded that promostion trought social networks has a significant effect on the sales at Klinik Selera in Bangkinang City. The closeness of the relationship between promotion throught social media varable on sales at Klinik Selera in Bangkinang City is very strong because the correlation coefficient (r) value is obtained 92,2%.